RIMEGEPANT AS A NOVEL THERAPEUTIC OPTION FOR MIGRAINE: A SYSTEMATIC REVIEW OF SAFETY AND TOLERABILITY - Zarzycka, Weronika; Skrzypek, Jakub; Fidut, Natalia; Szyprowski, Karol; Zioło, Kamila; Kisielewski, Maciej; Wawerska, Julia; Wrzosek, Weronika; Zugaj, Mateusz; Okliński, Bartosz (International Journal of Innovative Technologies in Social Science, 2026)
Objective. The aim of this paper is to analyze and evaluate currently available data and studies on the safety and tolerability of rimegepant in the treatment of migraine. Methodology. This literature review was based on articles from 2019–2026 available on PubMed and Google Scholar, including randomized controlled trials, open-label studies, and meta-analyses. Findings. Adverse reactions to rimegepant observed in clinical trials are largely mild or moderate. Serious adverse reactions and those leading to treatment discontinuation are rare and often considered unrelated to the drug. The most frequently reported adverse events in the databases were related to “general disorders and administration site conditions”. Rimegepant is safe for patients with high cardiovascular risk and no hepatotoxicity associated with this drug is observed. Compared to other available therapies, rimegepant also ranks highly in terms of both efficacy and safety. Conclusion. Rimegepant is a safe and well-tolerated oral medication for both acute and preventative migraine treatment. It is also a good alternative to other poorly tolerated or contraindicated migraine drugs.